Note that 2 3 − 1 3 = 7 is odd and 3 3 − 2 3 = 1 9 is also odd.
For any integer n , is it always true that n 3 − ( n − 1 ) 3 is odd?
If true, can you prove this? If false, can you find a counter example?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
n 3 − ( n − 1 ) 3 ≡ n − ( n − 1 ) = 1 ( m o d 2 )
Write out n 3 − ( n − 1 ) 3 in full
= n 3 − n 3 + 3 n 2 − 3 n + 1
= 3 n 2 − 3 n + 1
If n is even, let n = 2 c , where c is an integer, and replace all n 's with 2 c
Odd numbers can be expressed as 2 c + 1
= 3 ( 2 c ) 2 − 3 ( 2 c ) + 1
= 3 ( 4 c 2 ) − 6 c + 1
= 1 2 c 2 − 6 c + 1
= 2 ( 6 c 2 − 3 c ) + 1 This is in the form of an odd number, so if n is even, n 3 − ( n − 1 ) 3 is odd.
If n is odd, let n = 2 c + 1 , where c is an integer.
= 3 ( 2 c + 1 ) 2 − 3 ( 2 c + 1 ) + 1
= 1 2 c 2 + 1
= 2 ( 6 c 2 ) + 1 Again, this is in the form of an odd number, so if n is odd, n 3 − ( n − 1 ) 3 is odd.
Since n 3 − ( n − 1 ) 3 is odd when n is odd & n is even, n 3 − ( n − 1 ) 3 is always odd when n is an integer.
Problem Loading...
Note Loading...
Set Loading...
n 3 − ( n − 1 ) 3 = n 3 − ( n 3 − 3 n 2 + 3 n − 1 ) = 3 n 2 − 3 n + 1 = Always odd 3 n ( n − 1 ) Always even + 1
Note that n ( n − 1 ) is always even, because either n or n − 1 is even. Therefore 3 n ( n + 1 ) + 1 is always odd. True